Венчурний бізнес в Україні в умовах воєнного часу - Литвин, І. В.; Булак, Ю. В.; Lytvyn, Iryna; Bulak, Yuliia (Видавництво Львівської політехніки, 2022)
У статті розглянуті тенденції розвитку венчурного бізнесу в Україні, досліджено його сучасний стан в умовах війського стану. Вивчені основні джерела фінансування стартап-проєктів, визначені та проаналізовані історії успіху провідних вітчизняних стартапів, розкрита проблематика формування та становлення вітчизняного стартап бізнесу. Автори проаналізували перспективи розвитку стартап-індустрії України, можливості її відновлення до показників довоєнного стану.

The article examines the trends in the development of venture business in Ukraine and examines its current state in the conditions of martial law. The main sources of funding for start-up projects were studied, the success stories of leading domestic start-ups were identified and analyzed, and the problems of the formation and formation of domestic start-up businesses were revealed. The authors analyzed the prospects for the development of the startup industry in Ukraine and the possibilities of its restoration to pre-war indicators. The article examines the essence and history of the introduction of venture investment mechanisms in Ukraine and identifies the peculiarities of the formation and development of domestic start-up companies. The authors analyzed the trends in the development of the venture capital market in the pre-war period in the segment of individual players of the investment market – joint venture investment institutions. The article defines the positions of Ukraine and its cities in the global rankings of the best ecosystems for startups and outlines the most popular high-tech industries for investors in local startup projects in pre-war times. The authors analyzed the branch-based local startups and investigated the profile types of the Ukrainian startup based on the criteria of the number of cofounders, duration of work on the market, sources of financing, level of profitability, and organizational forms of entrepreneurship. The article analyzes the factors hindering the growth of the national venture capital market and the development of the local startup industry, as well as highlights the priority areas of their support in wartime conditions. Many factors were added to the risks of innovative activity in the conditions of martial law startups, which disrupted the continuity and normal flow of business processes of national startup companies. The local startup community faced the problems of living in conditions of brutal hostilities, and therefore the issue of employee safety, their relocation to fairly safe places of residence, the relocation of valuable technological equipment, and servers, and the restoration of access to the Internet became the primary factors for the creation of startup teams and recovery. their work in war conditions. The suspension of funding of startup projects by foreign investors and the lack of own resources force emigrant startups and their employees with their family members to safe countries of the world, which is also a problem for the survival of the Ukrainian startup ecosystem.
Venture businnes in Ukraine in wartime conditions
Keywords: венчурний бізнес; стартап-індустрія; стартапери; інноватори; венчурне фінансування; venture business; startup industry; startups; innovators; venture financing; 330.341.1; 334